Effects of the liberalization of agricultural markets, assessments on the rural development policies implemented in Mexico - Schwentesius Rindermann, Rita; Martínez-Carrasco Pleite, Federico; Perní Llorente, Angel (Revista Mexicana de Ciencias Agrícolas, 2018)
Poverty in rural areas of countries with medium income, as in the case of the Mexican economy, is still one of the priorities in their development agendas. The efforts that have been made in the scope of rural development and agrarian policies have been important in the majority of Latin American countries, and Mexico has been one of the countries in which the largest budgetary effort has been aimed at this purpose. The advances in the growth of the levels of well being of the rural population have been limited, and for this reason, this work suggests the study, by means of a questionnaire sent to experts on the sector, of the impact of market liberalization policies implemented since the 1990’s. The analysis of the qualitative information gathered from experts provides their valuable opinions on their assessment of the current structure on local development policies implemented in Mexico, with numerous aspects being objects discussion, with the sole purpose of proposing a modest reflection that, in at least some cases, may guide possible suggestions for the modification of policies implemented from their public administrations.
Keywords: poverty; market liberalization; public policies